Faktor-faktor yang berhubungan dengan kelengkapan imunisasi pada balita suspek campak di Puskesmas - Kasriani, Kasriani; Listiyaningsi, Erlin; Saputra, Hermawan (Universitas Faletehan, 2025)
Approximately 140,000 global child deaths each year are caused by measles, making measles a major focus in public health aspects. In 2021, there were 489 suspected measles cases in DKI Jakarta. In this case, in 2022, Cilincing District contributed 389 measles cases. Measles can be prevented by immunization. Cilincing District has an achievement of 98.3% for the measles immunization program. However, with this achievement, measles cases in Cilincing District are still quite high. This study aims to determine the factors associated with suspected measles cases in toddlers and the completeness of immunization obtained. Cross-sectional is the design in this study with a sample size of 220 taken by purposive sampling. Data analysis was carried out using the chi square test. The results of the analysis in this study found a relationship between the completeness of measles immunization with age (p-value 0.042), education (p-value 0.002), employment (p-value 0.009), attitude (p-value <0.001), availability of health facilities (p-value 0.010), and ease of access (p-value 0.049). However, it is known that the knowledge variable does not have a significant relationship with the completeness of measles immunization. The government and public health programs should target factors that have been proven to have an influence, such as increasing access to services, support for working mothers, and campaigns that form positive attitudes towards immunization.